MENGHIDUPKAN SEMANGAT FOUNDING FATHERS INDONESIA DALAM MEWUJUDKAN BEYOND ECONOMIC MAN: IDEOLOGI BARU AKUNTANSI - Widianingsih, Luky Patricia (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
Indonesia has founders with great minds and visionaries, and even revolutionaries. So, it is appropriate to explore the spirit of these ideas as a cure for various pathologies inherent in modern accounting today. This study aims to revive the thoughts of the four Indonesian triads, the Founding Fathers, namely Ir. Soekarno, Moh. Hatta, Sutan Sjahrir, and Tan Malaka then used the idea as a derivative of ideological synthesis born from the spirit of their thinking. This thinking is then used further as a basis for giving birth to a new imagination of accounting. Thoughts of the figures narrowed to the ideology of Pancasila. The new accounting is accounting, whose practice is accountability to God, fully humanizes humans, brings a unifying spirit of brotherhood, and is led in the practice of people-oriented wisdom in order to realize justice and prosperity for all people.Â